The Influence of Cultural Differences on Overbooking Compensation Strategies and Empirical Analysis: A Case Study of the Catering Industry - Wu, Xinrui; Zhang, Ziyuan; Zhou, JingYi (SHS web of conferences, 2025)
This research takes the catering industry as research subject to investigate the systematic impacts of cultural differences on overbooking compensation strategies. Drawing on three illustrative cases: a French Michelin-starred establishment, the Chinese hot-pot giant Haidilao, and Japan’s Sushi No Kami, the paper proposes a multi-layered analytical framework: encompassing value orientations, communication modalities, legal constraints, and psychological drivers—to explicate how cultural contexts inform both the structure and delivery of compensation. The comparative analysis reveals that, in individualistic regions (notably Europe and North America), costumers favor explicitly articulated, written compensation policies and access to exclusive, non-monetary experiences. Conversely, in China’s high-context, collectivist environment, rapid logistical coordination paired with “face-saving” vouchers or complimentary offerings proves most efficacious. In Japan, where relational sincerity and long-term bonds predominate, personalized gestures such as handwritten apologies and bespoke gifts maximize customer goodwill. Building on these findings, the paper advocates three strategic imperatives: (1) calibrate compensation thresholds and formats to cultural dimensions; (2) integrate behavioral-economic interventions,such as “seat-locking” mechanismsor positive framing techniques to shape consumer expectations; and (3) harness big-data analytics and AI-driven sentiment monitoring to dynamically adjust compensation schemes. The study furnishes both theoretical advances and practical guidelines for multinational restaurant operators seeking to harmonize cultural attunement with operational resilience.